Comparison of Post-Failure Strength of Micro-cracked Marble with Hoek-Brown Failure Criterion - Mahmutoğlu, Yılmaz; Şans, Gökhan (Mühendislik bilimleri dergisi, 2020)
Failure criteria of rock mass is the most important base for designing of surface and underground structures. However, behavior of jointed rock mass and its failure criteria are the controversial subjects of rock mechanics. Main reasons for this discussion are problems during or after the geotechnical application. However, some of the experimental and theoretical approaches are often preferred as they are practical, compatible with engineering considerations, and assist in decision-making process. On the other hand, the differentiation in the scale of the geosystem, which varies depending on the scale of geotechnical application, building process, and time, means that the failure conditions will also change. It is clear that the Mohr-Coulomb failure criterion, which is widely used in practice, cannot exactly represent discontinuous geo-environments (fractured rock) consisting of joint systems. Since the rock generally has a discontinuous character, it has been researched since the 1970s, and the Hoek-Brown failure criterion, put forth in the 1980s and modified many times until today, is widely accepted in application. Nevertheless, it is known that the empirical parameters used in this failure criteria proposed for different types of rocks are also open to discussion. In this paper, the results of the mechanical tests conducted on the previously-fissured model material, which is physically similar to rock mass are discussed. Marble samples whose grain boundaries were disturbed by cyclic thermal treatment were used as the model material. Post-failure curves of model material obtained from continuous failure state triaxial tests were compared with Hoek-Brown Failure Criteria. In conclusion, it was shown that the failure envelopes representing intergranular failure in the post-failure phase were similar and comparable to the Hoek-Brown Failure Criterion. However, it is found out that the post-failure strength in low confining stress may be lower than that of estimation by the Hoek-Brown criterion. Experimental studies have also shown that intergranular failure will develop among structural weaknesses in rock masses, and therefore the strength parameters commonly used in practice will depend on the size of geo-application.